Paternal Tobacco Smoke Correlated to Offspring Asthma and Prenatal Epigenetic Programming - Wu, Chih-Chiang; Hsu, Te-Yao; Chang, Jen-Chieh; Ou, Chia-Yu; Kuo, Ho-Chang; Liu, Chieh-An; Wang, Chih-Lu; Chuang, Hau; Chen, Chie-Pein; Yang, Kuender D. (Frontiers in Genetics, 2019)
Rationale: Little is known about effects of paternal tobacco smoke (PTS) on the offspring’s asthma and its prenatal epigenetic programming. Objective: To investigate whether PTS exposure was associated with the offspring’s asthma and correlated to epigenetic CG methylation of potential tobacco-related immune genes: LMO2, GSTM1 or/and IL-10 genes. Measurements and Main Results: In a birth cohort of 1,629 newborns, we measured exposure rates of PTS (23%) and maternal tobacco smoke (MTS, 0.2%), cord blood DNA methylation, infant respiratory tract infection, childhood DNA methylation, and childhood allergic diseases. Infants with prenatal PTS exposure had a significantly higher risk of asthma by the age of 6 than those without (p = 0.026). The PTS exposure doses at 0, <20, and ≧20 cigarettes per day were significantly associated with the trend of childhood asthma and the increase of LMO2-E148 (p = 0.006), and IL10_P325 (p = 0.008) CG methylation. The combination of higher CG methylation levels of LMO2_E148, IL10_P325, and GSTM1_P266 corresponded to the highest risk of asthma by 43.48%, compared to other combinations (16.67–23.08%) in the 3-way multi-factor dimensionality reduction (MDR) analysis. The LMO2_P794 and GSTM1_P266 CG methylation levels at age 0 were significantly correlated to those at age of 6. Conclusions: Prenatal PTS exposure increases CG methylation contents of immune genes, such as LMO2 and IL-10, which significantly retained from newborn stage to 6 years of age and correlated to development of childhood asthma. Modulation of the LMO2 and IL-10 CG methylation and/or their gene expression may provide a regimen for early prevention of PTS-associated childhood asthma. Descriptor number: 1.10 Asthma Mediators. Scientific Knowledge on the Subject: It has been better known that maternal tobacco smoke (MTS) has an impact on the offspring’s asthma via epigenetic modification. Little is known about effects of paternal tobacco smoke (PTS) on the offspring’s asthma and its prenatal epigenetic programming. What This Study Adds to the Field: Prenatal tobacco smoke (PTS) can program epigenetic modifications in certain genes, such as LMO2 and IL-10, and that these modifications are correlated to childhood asthma development. The higher the PTS exposure dose the higher the CG methylation levels are found. The combination of higher CG methylation levels of LMO2_E148, IL10_P325 and GSTM1_P266 corresponded to the highest risk of asthma. Measuring the DNA methylation levels of certain genes might help to predict high-risk populations for childhood asthma and provide a potential target to prevent the development of childhood asthma.